2005
DOI: 10.1080/10288457.2005.10740583
|View full text |Cite
|
Sign up to set email alerts
|

Chemical concepts inventory of Grade 12 learners and UP foundation year students

Abstract: Incoming chemistry students at tertiary institutions have a variety of academic backgrounds that influence their prospects of success at first-year level. The proficiencies of incoming students are currently changing due to the introduction of outcomes-based education and new syllabi for physical science in secondary schools. In order to ensure a smooth transition from secondary to tertiary education, university lecturers should be well informed about the content knowledge, conceptual understanding and skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
1
8
0
8
Order By: Relevance
“…Indeks CRI (Certainty of Response Index) adalah skala keyakinan responden (siswa) dalam menjawab pertanyaan (Potgieter et al, 2005). Instrumen yang telah disusun diuji coba terlebih dahulu untuk mengetahui validitas dan reliabilitas instrumen.…”
Section: Metode Penelitianunclassified
“…Indeks CRI (Certainty of Response Index) adalah skala keyakinan responden (siswa) dalam menjawab pertanyaan (Potgieter et al, 2005). Instrumen yang telah disusun diuji coba terlebih dahulu untuk mengetahui validitas dan reliabilitas instrumen.…”
Section: Metode Penelitianunclassified
“…He reported that if students answer correctly and the reasons are also true, despite the low level of confidences, it can be concluded that those students understand the concepts but are not confident enough in answering the given questions. The CRI classification modified by Potgieter et al (2005) and Hakim et al (2012) can be seen in Table 1. …”
Section: Methodsmentioning
confidence: 99%
“…The CRI scale used in this study was a modification from Hasan et al (1999), performed by Potgieter et al (2005) with four scales: 1 = Guessing; 2 = Unsure; 3 = Sure; 4 = Very Sure. Low CRI level (1-2) shows students' hesitancy in answering the questions.…”
Section: Methodsmentioning
confidence: 99%
“…The use of confidence levels in mathematics or science education research is limited, but has been applied in chemistry (Potgieter, Rogan & Howie, 2005), mathematics (Yazdani, 2006), biology (Bowen & Roth, 1999) and mechanics (Oliva, 1999;Reif & Allen, 1992). Planinic et al (2006) have also used certainty of response (self-reported confidence) coupled with performance to explore relative strengths of misconceptions in different areas of physics.…”
Section: Literature Reviewmentioning
confidence: 99%